Studies on the formation, temporal evolution & forensic applications of camera fingerprints - Kuppuswamy, R. (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2004)
A series of experiments was conducted by exposing negative film in brand new cameras of different make and model. The exposures were repeated at regular time intervals spread over a period of two years. The processed film negatives were studied under a stereomicroscope (x1 O-x40) in transmitted illumination for the presence of the characterizing features on their four frame-edges. These features were then related to those present on the masking frame of the cameras by examining the latter in reflected light stereomicroscopy (x1 O-x40). The purpose of the study was to determine the origin and permanence of the frame-edgemarks, and also the processes by which the marks may probably alter with time. The investigations have arrived at the following conclusions: i) the edge-marks have originated principally from the imperfections received on the film mask from the manufacturing and also occasionally from the accumulated dirt, dust and fiber on the film mask over an extended time period. ii) The edge profiles of the cameras have remained fixed over a considerable period of time so as to be of a valuable identification medium. iii) The marks are found to be varying in nature even with those cameras manufactured at similar time. iv) The influence of f/number and object distance has great effect in the recording of the frame-edge marks during exposure of the film. The above findings would serve as a useful addition to the technique of camera edge-mark comparisons.